Effects of Physical Activity on the Association Between Interoception and Anxiety in Finnish Adults - Wilson, Lindsey (2018)
Interoception is the ability to sense one’s physical perturbations in the body. Interoception has gained relevance in psychological studies of emotion within the past decade, as the brain structures responsible for relaying interoceptive signals also share structures responsible for emotion-processing. Of note, a heightened sense of interoception has been linked with increased measures of anxiety, a common mental illness that may be of detriment to those of which it afflicts. Physical exercise has consistently shown to reduce anxiety and may serve as a therapeutic form of interoceptive exposure. Thus, identifying how physical exercise impacts the relationship between interoception and anxiety should be explored. This study investigated the differences that physical activity may have on the intensity levels of anxiety in participants with high levels of interoception. Participants (n=50; male=22, female= 28) completed an objective measure of interoception in the form of a heartbeat discrimination task, a self-report of hours of weekly physical activity, and a subjective measure of anxiety (Beck Anxiety Inventory). Independent t-test comparisons identified no significant statistical difference between anxiety levels of participants varying in physical activity level regardless of high levels of interoception accuracy. Relevance and implications of these finding to existing and future research are discussed.